Investigating Teacher’s Strategies in Teaching English Language to Young Learner: A Comparative Study between 1st and 3rd Grade of Elementary School - Durratu Fakhria Nasution; Fahriany (Institut Agama Islam Negeri Palopo, 2025)
This study investigates the comparative teaching strategies employed by English teachers for 1st and 3rd-grade elementary school students, emphasizing the need to tailor approaches to the developmental stages of each age group. This research is done by qualitative method where classroom observation and interview were used to collect the data. An English teacher at SDI Miftahul Diniyah Pamulang was the subject in this research. This research found that for 1st graders, characterized by concrete thinking, short attention spans, and the early stages of language acquisition, effective strategies include play-based learning, phonics-focused activities, and the use of visual aids. Structured routines and immediate feedback are essential for classroom management and student engagement. Conversely, 3rd graders, who exhibit emerging abstract thinking, longer attention spans, and advanced language skills, benefit from project-based learning, reading comprehension activities, and discussions that foster critical thinking. Classroom management for 3rd graders involves clear expectations and opportunities for self-management, as they are more independent and responsible. The study also highlights the social and emotional development differences, with 1st graders needing structured social interaction and emotional expression activities, while 3rd graders thrive on peer learning and collaborative projects. This analysis underscores the importance of adapting teaching strategies to align with the cognitive, social, and emotional development of young learners, thereby enhancing their educational experiences and outcomes.